Isolasi dan Elusidasi Senyawa Flavonoid dari Biji Alpukat (Persea americana Mill.) - Feliana, Kiki; Mursiti, Sri; Harjono, Harjono (Indonesian Journal of Chemical Science, 2018)
Avocado (Persea americana Mill.) is a plant that can flourish in tropical regions like Indonesia. Avocado seeds have the hypoglycemic effect and can be used for traditional medicine. The ethanol extract of avocado seeds contains several secondary metabolite compounds such as alkaloids, triterpenoids, tannins, flavonoids, and saponins. Aims of this study are to identify groups and structures of flavonoid compounds in avocado seeds. 4,000 g of avocado seed powder produces ethanol 170 gcondensed extract with maseration process. 100 g of viscous ethanol extract using ethyl acetate and water yielded 25.6 g of ethyl acetate extract with partition process. The separation of ethyl acetate extract by Thin Layer Chromatography (TLC) with G-F254 stationary phase and n-butanol mobile phase : acetic acid: water (BAA) phase (4:1:5) produces positive fractions containing flavonoids.Results of avocado seeds isolate analysis with FT-IR showed that isolate has OH functional group, CH aliphatic, C=O, C=C aromatics, and CH aromatic, while analysis with UV-Vis spectrophotometer showed the absorption peak at 285 nm and 320 nm wavelength, so the hypothesis of isolate is flavonoid compound flavanon group with hydroxy group at C-7 atom.